2021
DOI: 10.2147/lra.s300054
|View full text |Cite
|
Sign up to set email alerts
|

The Current Practice of Spinal Anesthesia in Anesthetists at a Comprehensive Specialized Hospital: A Single Center Observational Study

Abstract: Background Spinal anesthesia block is the most widely practiced anesthesia technique due to its safety margin. It is an invasive procedure that could be associated with a variety of complications like total spinal, cardiovascular collapse, meningitis, paralysis, and even death. The aim of this study to assess the current practice of spinal anesthesia. Methods A Cross-sectional study design was conducted in Debre Tabor Comprehensive Specialized Hospital from November 01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The commission develop check list for safety steps to decrease infection and toxicity before performing a regional block [11] . A study in Debretabor specialized hospital reported all of the anesthetists did not wash their hands, wore a sterile gown, and draped the back of the patient with fenestrated drapes in a sterile fashion [12] . Another study conducted at the University of Gondar by Chekol W et al, found as all anesthetists did not wash their hands and wear sterile gowns [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The commission develop check list for safety steps to decrease infection and toxicity before performing a regional block [11] . A study in Debretabor specialized hospital reported all of the anesthetists did not wash their hands, wore a sterile gown, and draped the back of the patient with fenestrated drapes in a sterile fashion [12] . Another study conducted at the University of Gondar by Chekol W et al, found as all anesthetists did not wash their hands and wear sterile gowns [13] .…”
Section: Discussionmentioning
confidence: 99%
“…4 Various pharmacological agents have been used for this purpose depending upon time of surgery, anesthetist choice and safety of medication. 5 Still a lot of research has been going on in this field to find safest and most efficacious option for this purpose and even a lot of combinations have also been tried to potentiate the effect of each other. 6 Comparison of various single and combination agents have been performed to look for best option for SA for perineal surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is widely used in modern anesthesia and is very popular due to its rapid onset and recovery easy titration (1,2). However, intense pain on injection as a bad experience is its major adverse effect, ranking seventh among 33 unsolved clinical problems (3). In untreated cases, it has been demonstrated that the incidence of propofol injection pain (PIP) varies from 28% to 90% (4,5).…”
Section: Introductionmentioning
confidence: 99%